Inductive reasoning skills: Identification of student errors using APOS theory - Ilham Muhammad; Lilis Marina Angraini; Syarul Ramadhan (EduMa: Mathematics education learning and teaching, 2025)
Math problem-solving mistakes made by students need to be treated more seriously since, if left unattended, they may affect students' comprehension of the following mathematical ideas. This study aims to identify students’ errors while attempting to solve mathematical problems of inductive reasoning ability on the material of powers and roots. This study adopts a qualitative method with descriptive research. The participants in this study were 24 students of class IX A at SMPN 2 Pelalawan. The research methods used are tests, interviews, and triangulation. The results showed that students had low inductive reasoning abilities so they made mistakes in solving problems. Based on the APOS theory (action, process, object, and schema), there are four student errors in solving math problems, namely: 1) incorrect interpretation: students do not grasp the meaning and objective of the questions; 2) conceptual error: misunderstood the multiplication of powers; 3) procedural errors: they occur when students conclude problems without adhering to a process; 4) Technical errors: Students frequently make errors while multiplying powers because they do not understand the concept. Regarding the APOS theory, based on the data analysis students only arrived at the first phase, namely the action phase